'Lol you go to gulag': The role of Sassy Socialist Memes in Leftbook1. Issue 1 (1st March 2020) - Bowen, Bernadette
Since 2016, a culture of participatory leftism has emerged on Facebook that has yet to be substantially documented. Scholars have established ideographic criticism of memes as a critical/cultural tool for analysis. However, there is little to no work on broader, systems-based analyses of alternative social media platforms, and the role they play in the creation and maintenance of political identities. These socially mediated communities, alternatively known as Leftbook (or Left Facebook), advertise themselves as places to learn about Marx, socialism and philosophies centred on labour, revolution and worker freedom. Research from traditional online group pages suggests there is a distinct split between neutral observers and harsh critics of Leftbook. These online spaces often result in odd, hilarious and peculiar behaviours that the untrained eye is quick to dismiss as meaningless Internet drivel. However, humour and satire have long been used tactfully by counterculture organizations/movements to communicate the absurdity of the status quo. For instance, Waisanen argued that unlikely sources of comedic rhetorical criticism creatively influence and critically reframe political discourse; guiding audiences towards new possibilities of insight and democratic civil discourse. Using Johnson's explanations of memetics as a guiding theory, I discuss Burke's various works on human paradox, identification, Dramatism and the comic frame to provide insight on notions of: identity performance, 'slacktivism' and burgeoning political resonance within this digital environment. I code preliminary themes of the post content of one Leftbook page, 'Sassy Socialist Memes', over the course of a month. My guiding research questions are '[a]s platforms such as Leftbook become environmental, how do they contribute to a mode of socio-political identity construction for members of the Left?' and '[a]s extensions of political identity, how does the 'Sassy Social Memes' page impact experiences of political organizing and engagement?'.